Perawatan Structural Firefighting Suit untuk Menunjang Kinerja Personel PKP-PK - Muhammad Firas Nur Fakhriyanto; Saptandri Widiyanto; Rini Sadiatmi (MANAJEMEN, 2025)
This study aims to analyze the maintenance of Structural Firefighting Suits used by Aircraft Rescue and Firefighting (ARFF) personnel at Jenderal Ahmad Yani Airport, Semarang. The research employed a qualitative case study through observation, interviews, documentation, and literature review. The findings indicate that limited maintenance practices, such as airing the suits without thorough cleaning, caused damage including tears, mold, and detached fasteners, which reduced comfort, safety, and operational effectiveness. Regular and scheduled maintenance is therefore essential to extend the service life of PPE and ensure safety performance of ARFF personnel in emergency situations.